A rare case of conspiracy by lawful means - LEE, Pey Woan (Institutional Knowledge at Singapore Management University, 2014)
Conspiracy by lawful means is a well-known anomaly in the law of torts. The anomaly lies in the fact that the tort imposes liability on two or more persons acting in concert to pursue a course of conduct that is otherwise lawful when committed by a sole actor. Of course, it is a critical element of the tort that the conspirators must have acted with the predominant intention to cause harm to the victim, but it is well settled that malicious intent is not, by itself, a sufficient basis for founding liability. It would thus seem that it is the fact of combination that somehow magically transforms a lawful course of action into a tortious one. Despite its somewhat perplexing foundation, however, no serious attempt has been made to expunge this tort from the law. Perhaps, it is thought that the tort would in any event have little or no application in the commercial context, where the motive for injuring another usually lies in the desire to advance one’s own interests, in which case the injurer could not be said to have acted with the predominant intention to injure another. Against this backdrop, the case of SH Cogent Logistics Pte Ltd v Singapore Agro Agricultural Pte Ltd [2014] SGHC 203 (“SH Cogent”) is remarkable, for in this case the High Court upheld an allegation of lawful means conspiracy in the context of a purely commercial dispute.